(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Soft computing is a growing set of approaches that strive to provide resilience, tractability, and cheap cost by leveraging tolerance for imprecision uncertainty and partial truth. It may appear to be a highly appealing alternative to a totally digital system, but there are several traps in store for researchers attempting to implement this new and intriguing technology. Software computing offers an appealing way to represent ambiguity in human thought with real-world uncertainty. The main approaches of soft computing include fuzzy logic, neural networks, and evolutionary computation. Both neural networks and fuzzy systems can be utilised for nonlinear processing.